Role of high-mobility group box 1 in patients with acute obstructive suppurative cholangitis-induced sepsis - Singh A; Feng Y; Mahato N; Li J; Wu C; Gong J (Dove Medical Press, 2015)
Akanand Singh,1 Yi Feng,1 Nisha Mahato,2 Jinzheng Li,1 Chuanxin Wu,1 Jianping Gong1 1Chongqing Key Laboratory of Hepatobiliary Surgery and Department of Hepatobiliary Surgery, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 2Department of Prosthodontics, The Affiliated Hospital of Stomatology, Chongqing Medical University, Chongqing, People's Republic of China Background: High-mobility group box 1 (HMGB1) is a proinflammatory cytokine that plays an active role during the pathogenesis of inflammatory processes. The primary aim of this study was to detect whether HMGB1 is involved in the pathogenesis of acute obstructive suppurative cholangitis (AOSC). Methods: We collected peripheral blood samples from 23 patients with AOSC and 23 healthy volunteers who served as normal controls. All participants were tested for HMGB1 mRNA level, HMGB1 protein, tumor necrosis factor alpha (TNF-alpha), and interleukin 10 (IL-10). HMGB1 mRNA levels were tested using real-time polymerase chain reaction. HMGB1 protein expression was measured using Western blot. TNF-alpha and IL-10 were tested using enzyme-linked immunosorbent assay. Results: The expression of HMGB1 mRNA and HMGB1 protein was higher in the AOSC group than in the normal controls (P<0.01), and the levels gradually decreased to normal after treatment of the disease (P<0.01). The content of TNF-alpha and IL-10 in peripheral blood of patients with AOSC was significantly higher than that of normal controls (P<0.01) but decreased to normal levels after the necessary treatment (P<0.01). Conclusion: The levels of HMGB1 mRNA and HMGB1 protein were elevated in patients with AOSC, which may play an important role in the inflammation of the bile duct and appears to be associated with the development of sepsis. This suggests the importance of monitoring HMGB1 levels in the management of AOSC-induced sepsis. Keywords: AOSC, HMGB1, interleukin 10, TNF-alpha, sepsis, inflammation